Effect of host-mimicking medium and biofilm growth on the ability of colistin to kill Pseudomonas aeruginosa. Issue 12 (30th December 2020) - Sweeney, Esther; Sabnis, Akshay; Edwards, Andrew M.; Harrison, Freya
Abstract : In vivo biofilms cause recalcitrant infections with extensive and unpredictable antibiotic tolerance. Here, we demonstrate increased tolerance of colistin by Pseudomonas aeruginosa when grown in medium that mimics cystic fibrosis (CF) sputum versus standard medium in in vitro biofilm assays, and drastically increased tolerance when grown in an ex vivo CF model versus the in vitro assay. We used colistin conjugated to the fluorescent dye BODIPY to assess the penetration of the antibiotic into ex vivo biofilms and showed that poor penetration partly explains the high doses of drug necessary to kill bacteria in these biofilms. The ability of antibiotics to penetrate the biofilm matrix is key to their clinical success, but hard to measure. Our results demonstrate both the importance of reduced entry into the matrix in in vivo -like biofilm, and the tractability of using a fluorescent tag and benchtop fluorimeter to assess antibiotic entry into biofilms. This method could be a relatively quick, cheap and useful addition to diagnostic and drug development pipelines, allowing the assessment of drug entry into biofilms, in in vivo -like conditions, prior to more detailed tests of biofilm killing.